Research Advisor & Assistant Professor of CommercePG and Research Department of CommerceSt. Joseph’s College, Trichy - Karthiga, B.; Sujatha, V. (International Journal of Psychosocial Rehabilitation, 2020)
Electronic Business commonly referred to as "e-Business" or "e-business", or an internet business, may be defined as the application of information and communication technologies (ICT) in support of all the activities of business. Commerce constitutes the exchange of products and services between businesses, groups and individuals and can be seen as one of the essential activities of any business. Electronic commerce focuses on the use of ICT to enable the external activities and relationships of the business with individuals, groups and other businesses. The term "e-business" was coined by IBM’s marketing and Internet teams in 1996.